The human genome as the common heritage of humanity - Kabata, Faith; Thaldar, Donrich (Frontiers in Genetics, 2023)
While debate on the international regulation of human genomic research remains unsettled, the Universal Declaration on the Human Genome and Human Rights, 1997 qualifies the human genome as “heritage of humankind” in a symbolic sense. Using document analysis this article assesses whether, how and to what extent the common heritage framework is relevant in regulation of human genomic research. The article traces the history of the Human Genome Project to reveal the international community’s race against privatization of the human genome and its resulting qualification as the common heritage of humanity. Further, it reviews the archival records of UNESCO’s International Bioethics Committee to discover the rationale for qualifying the human genome as common heritage of humankind. The article finds that the common heritage of mankind framework remains relevant to the application of the human genome at the collective level. However, the framework is at odds with the individual dimension of the human genome based on individual personality rights. The article thus argues that the right to benefit from scientific progress and its applications offers an alternative international regulatory framework for human genomic research.